The Role of Digital Literacy in Preventing Online Gambling Among the Younger Generation - Rolita, Ayu; Yulistia, Yulistia (Indonesian Journal of Research and Service Studies, 2024)
The rapid expansion of digital technology has significantly increased young people's exposure to online gambling, making it a growing social, economic, and public health concern. While government interventions have primarily emphasized law enforcement and website blocking, preventive approaches through digital literacy remain underexplored. This study aims to analyze the role of digital literacy in preventing online gambling among young people by identifying its key dimensions and examining their contribution to strengthening preventive behavior. The study employed a literature review approach using secondary data collected from peer-reviewed journal articles and reports published by reputable international organizations and government institutions. The selected literature was analyzed through qualitative content analysis and thematic synthesis to identify recurring patterns and conceptual relationships. The findings reveal that digital literacy contributes to online gambling prevention by enhancing critical thinking, digital ethics, risk awareness, self-regulation, and digital resilience. Furthermore, effective prevention requires collaboration among educational institutions, families, governments, and digital platform providers to establish a comprehensive digital ecosystem. The study proposes an integrated conceptual framework positioning digital literacy as a behavioral prevention mechanism that connects technological competence with responsible digital decision-making. In conclusion, strengthening digital literacy represents a sustainable preventive strategy for reducing young people's vulnerability to online gambling while providing theoretical and practical implications for educational policy, digital governance, and future research.